Brain Dominance and its relationship to Tolerance for Cognitive Ambiguity and Academic Achievement among gifted and normally developing secondary stage female students in Makkah Al-Mukarramah - Alzahrani, Elham Majhoud (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the relationship between brain dominance, cognitive ambiguity tolerance and academic achievement among gifted and normally-developing secondary stage female students in Makkah using the Descriptive Correlational Comparative approach. Al-Zoubi’s Brain Dominance Scale (2017) and Budner’s Ambiguity Tolerance Scale (1962) were applied to a stratified random sample of (562) female students. The results indicated left-brain dominance among the normally-developing and integrated brain among the gifted; and that there is an average level of ambiguity tolerance among the female students. The results also showed a statistically significant negative relationship between the integrated brain and ambiguity tolerance; a statistically significant positive relationship between the left-brain and ambiguity tolerance; a statistically significant positive relationship between the left-brain and achievement. There were also statistically significant differences in achievement in favor of gifted students. The results of the three-way variance analysis also showed differences between the average responses of the right-brain attributed to the discipline variable in favor of the human discipline, and depending on the category in favor of the normally-developing students; differences in the left-brain attributed to the discipline variable in favor of the scientific discipline; differences in the integrated brain attributed to the category variable in favor of gifted students; and differences between the average responses on the ambiguity tolerance scale attributed to the interaction between (category and discipline) in favor of normally-developing female students in the human discipline. The research recommends the development of educational programs that take into consideration the different patterns of dominance, activate the functions of the non-dominant side, and increase levels of ambiguity tolerance among students.
Keywords: brain dominance; tolerance for cognitive ambiguity; academic achievement; gifted; secondary stage